2021
DOI: 10.3390/ma14185417
|View full text |Cite
|
Sign up to set email alerts
|

Surface Magnetization Reversal of Wiegand Wire Measured by the Magneto-Optical Kerr Effect

Abstract: The Wiegand wire is known to exhibit a unique feature of fast magnetization reversal in the magnetically soft region accompanied by a large Barkhausen jump. We clarified a significant difference between the magnetization reversals at the surface and at the entire cross section of a Wiegand wire. We conducted magnetization measurements based on the magneto-optical Kerr effect and applied conventional methods to determine the magnetization curves. The switching field of the magnetization reversal at the surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Typically, the magnetic properties of magnetic materials are expressed by measuring the major or minor hysteresis loops. Prior research has already investigated the magnetization reversal process of magnetic materials in detail by the magneto-optical Kerr effect (MOKE) [ 15 , 16 ]. Nonetheless, the information on the interactions or coercivity distributions cannot be feasibly obtained from the major hysteresis loop or the minor loop, as the MOKE can only evaluate the magnetization process on the surface of magnetic materials.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, the magnetic properties of magnetic materials are expressed by measuring the major or minor hysteresis loops. Prior research has already investigated the magnetization reversal process of magnetic materials in detail by the magneto-optical Kerr effect (MOKE) [ 15 , 16 ]. Nonetheless, the information on the interactions or coercivity distributions cannot be feasibly obtained from the major hysteresis loop or the minor loop, as the MOKE can only evaluate the magnetization process on the surface of magnetic materials.…”
Section: Methodsmentioning
confidence: 99%
“…If the sample comprises thin films or nanowires of a thin structure, the surface magnetization is similar to the surface layer or the whole sample. Nakamura et al showed that the surface magnetization of a Wiegand wire measured by MOKE is completely different from that of the whole layer or soft layer near the surface region [ 15 ]. Different magnetization at the surface is possible for bulk material, as well as a Wiegand wire of sub millimeter material.…”
Section: Methodsmentioning
confidence: 99%
“…A magnetic field camera based on the Faraday effect was used to directly observe magnetization reversal in Wiegand wires [17]. The magneto-optical Kerr effect was used to measure the magnetization on the surface of a Wiegand wire [18]. The magnetization of the various layers in the Wiegand wire can be identified using first-order reversal curve (FORC) diagrams [19][20][21].…”
Section: Introductionmentioning
confidence: 99%